perancangan convention dan exhibition di solo dengan pendekatan metafora - irfan siswanto; Anggraeni Dyah Sulistiowati (FAKULTAS TEKNIK UNIVERSITAS BUDI LUHUR, 2019)
Because the city of Solo has great business potential, stable economic growth, the number of tourism that continues to increase and successful city branding, the development in the city of Solo continues to grow. One of the developments planned by the government is MICE development in the city of Solo. MICE stands for